1999
DOI: 10.1046/j.1365-2958.1999.01619.x
|View full text |Cite
|
Sign up to set email alerts
|

Filamentous growth of Candida albicans in response to physical environmental cues and its regulation by the unique CZF1 gene

Abstract: Hyphal growth in the opportunistic fungal pathogen Candida albicans is believed to contribute to the virulence of the organism by promoting penetration of fungal cells into host tissue. In this study, stimulation of hyphal growth by a feature of the physical environment was demonstrated. Specifically, growth of cells embedded within a matrix promoted the formation of hyphae. The CZF1 gene, encoding a putative transcription factor, was shown to be involved in the regulation of hyphal growth under certain condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
248
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(270 citation statements)
references
References 42 publications
14
248
0
6
Order By: Relevance
“…Lee's and YPD ϩ 10% bovine serum media were used for hyphal induction (Lane et al, 2001b). YPS with 1% agar was used for colony morphology assay under embedded conditions (Brown et al, 1999).…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…Lee's and YPD ϩ 10% bovine serum media were used for hyphal induction (Lane et al, 2001b). YPS with 1% agar was used for colony morphology assay under embedded conditions (Brown et al, 1999).…”
Section: Strains and Culture Conditionsmentioning
confidence: 99%
“…This indicates the fine specificity and affinities of the ligand-binding pocket. Thus, the Czf1p-mediated matrix pathway (Brown et al, 1999;Giusani et al, 2002) is likely to involve different interactions of Bmh1p with ligands than the MAPK/cAMP pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For all experiments, strains were either made prototrophic for URA3 or uridine was included in the media. For filamentation in matrix, studies were performed basically as reported by Brown and co-workers (Brown et al, 1999;Giusani et al, 2002). Briefly, 100 cells were plated onto YPS agar and then overlaid with a second layer of YPS agar, or approximately 100 cells were mixed with 25 ml molten YPS agar (2 %) and poured into a Petri dish.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For selection of Ura 2 strains, CM-Ura medium was supplemented with 60 mg uridine ml 21 and 1 mg 5-fluoroorotic acid ml 21 (Kelly et al, 1987). For the colony morphology assay, YPS medium containing 1 % agar (Difco) was used (Brown et al, 1999). Synthetic low ammonium, Lee's, proline and GlcNAc media were prepared as described by Brown et al (1999).…”
Section: Strainsmentioning
confidence: 99%